The Figure in the Carpet - James, Henry, 1843-1916 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Figure in the Carpet" by Henry James is a short story first published in 1896. An unnamed narrator becomes obsessed with uncovering a hidden meaning in his favorite author's works$1 (Ba secret pattern the writer claims all critics have missed. As the narrator and his friends pursue this elusive literary mystery, their quest leads to unexpected revelations and tantalizing dead ends. The story explores the nature of artistic intention and the limits of critical interpretation, leaving readers to wonder whether the secret truly exists. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Figure_in_the_Carpet
Release date is 1996-09-01
Transcribed from the 1916 Martin Secker edition by David Price
Keywords: Short stories, American; Interpersonal relations -- Fiction; Women novelists -- Fiction; Critics -- Fiction; Secrecy -- Fiction